MENINGKATKAN KETERAMPILAN MOTORIK HALUS MELALUI AKTIVITAS MENGETUK PADA ANAK-ANAK KELOMPOK B DI PUSAT PENDIDIKAN ANAK USIA DINI BERINGIN INDAH BENGKULU SELATAN - Fadhlil Hadi; Andes Permadi; Arrendi Afrilliyan; Alfin Julianto; Ijayani; Nur Fathanah; Aldian Mapsur Putra (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2026)
The purpose of this study is to improve the motor skills of children in group B of Early Childhood Education (PAUD) by using banana stems as a medium. Through two cycles starting from planning, implementation, observation, and reflection is the method used to conduct this study. Ten children with a total of seven boys and three girls are the subjects of the study. Classroom Action Research (CAR) is the type of research used in this study. The methods used to collect data are observation, interviews, and documentation. The instruments used are assessment sheets and observation instruments. This study uses quantitative data analysis techniques using statistical analysis. The results showed that children's fine motor skills in the pre-cycle were 42.50%, in cycle 1 it was obtained 70.83% and cycle II reached 83.33%. This concludes that stamping activities using banana stems can improve fine motor skills in children in group B of PAUD Beringin Indah well and optimally.